World water demand and supply, 1990 to 2025: scenarios and issues - Seckler, D.; Amarasinghe, Upali A.; Molden, David J.; Silva, R. de; Barker, Randolph (International Irrigation Management Institute, 1998)
Presents two alternative scenarios of water demand and supply for 118 countries over the 1990 to 2025 period and develops indicators of water scarcity for each country and for the world as a whole. This study is the first step in IWMI's long-term research goal: to determine the extent and depth of water scarcity, its consequences for individual countries and what can be done about it.